Human resources management strategies in enhancing transportation performance and safety in Indonesia - Sarinah Sihombing; Juliater Simarmata; Astri Rumondang Banjarnahor; Sofwan Farisyi; Adisak Suvittawat (Goodwood Publishing, 2025)
Purpose: This study explores the strategic role of Human Resource Management (HRM) practices training and development, performance management, and organizational innovation in improving transportation performance and safety in Indonesia, while examining the moderating effect of employee welfare amid growing digital transformation and rising safety standard demands. Methodology: A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 360 respondents working in the land transportation sector across Indonesia through structured questionnaires. Results: The findings confirm that training and development, as well as performance management, significantly influence both organizational innovation and transportation safety. Organizational innovation also positively affects transportation performance, which in turn enhances safety. However, the moderating effect of employee welfare on the innovation–performance relationship was found to be statistically insignifican. Conclusions: High-quality HRM practices in training and performance management enhance operational performance and safety in Indonesia’s transportation sector. However, innovation’s full benefits require stronger welfare systems and integrated safety training, performance tracking, and inclusive innovation within HR strategies for workforce resilience. Limitations: This study finds employee welfare has not significantly moderated transportation performance through innovation. Most welfare initiatives remain basic and unaligned with strategic agendas, revealing a gap between employee well-being and organizational goals that may hinder long-term innovation sustainability. Contribution: This study validates the impact of training and performance management on transportation innovation and safety in developing countries, offering a framework for aligning HR strategies with digitalization and safety goals while emphasizing welfare policies that actively support innovation and performance excellence.